Pengaruh Senam Yoga Restorative Terhadap Tingkat Kecemasan Ibu Hamil Primigravida Trimester III di Kelurahan Sidorejo - Rosita Sari, Alda; Pitaloka, Dyah (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
The third trimester of pregnancy is a period that is vulnerable to psychological disturbances, particularly anxiety, especially among primigravida pregnant women who are facing childbirth for the first time. Anxiety is an emotional condition characterized by feelings of fear and worry accompanied by physiological and psychological responses, which, if not properly managed, may negatively affect maternal health and fetal development. One non-pharmacological intervention that can be used to reduce anxiety is Restorative Yoga, a form of yoga that emphasizes deep relaxation through gentle movements, controlled breathing, and the use of supportive props.This study aimed to determine the effect of Restorative Yoga on anxiety levels among third-trimester primigravida pregnant women in Sidorejo Village. This study employed a pre-experimental design with a one-group pretest–posttest ap-proach. The research was conducted in Sidorejo Village and involved 36 third-trimester primigravida pregnant women as respondents, selected using a non-probability sampling technique with purposive sampling. Anxiety levels were meas-ured using the Hamilton Anxiety Rating Scale (HARS) before and after the imple-mentation of restorative yoga exercises. Data analysis was performed using the Wil-coxon Signed-Rank Test.The results showed that before the intervention, most respondents experi-enced moderate anxiety (69.4%) and severe anxiety (5.6%). After the Restorative Yoga intervention, anxiety levels decreased, with the majority of respondents classi-fied as having mild anxiety (91.7%), and no respondents experienced severe anxie-ty. The Wilcoxon test showed a value of p = 0.000 (p < 0.05), indicating a statistical-ly significant difference in anxiety levels before and after the intervention. These findings indicate that Restorative Yoga is effective in promoting relaxation and re-ducing anxiety in pregnant women. Based on these findings, it can be concluded that restorative yoga exercise has a significant effect in reducing anxiety levels among third-trimester primigravida pregnant women in Sidorejo Village.